Community Participation in The Implementation of Waste Management Policies In Surabaya Main Waste Bank - Yuli Eka Fauziah; Bintoro Wardiyanto; Antun Mardiyanta (Program Pascasarjana Universitas Negeri Makassar, 2022)
The 2030 SDGs target will not be achieved as long as the environment is still polluted by wild waste. Wild waste is a problem that is closely related to households, where the city of Surabaya is free from the problem of illegal waste. Therefore, the participation of Surabaya City households in managing waste is the object of research. What drives households to participate in waste management activities, especially in BSIS, is discussed in this study. This research is a qualitative research with an interpretive social science approach. The research location was at BSIS where the data collection was obtained through literature, observation, documentation, and in-depth interviews with selected informants using a purposive technique. Checking the validity of the data used source triangulation and data analysis using qualitative data analysis techniques. The results of the study show that those who participate in BSIS are those who have economic motives or make BSIS a financial resource, have the skills to participate, carry out government commitments, adhere to the same social organization tradition, know the legal framework regarding waste banks, and have ease of accessing information.